2018
DOI: 10.1074/jbc.r117.001655
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-mediated signals that regulate mitochondrial biology

Abstract: For decades, lipids were assumed to fulfill roles only in energy storage and membrane structure. Recent studies have discovered critical roles for phospholipids, sphingolipids, and sterols in many cellular pathways, including cell signaling and transcriptional regulation. Frequently, lipids from these various classes work together to achieve defined cellular outcomes. Specific mitochondrial lipids are critical for proper assembly of the electron transport chain complexes and for effective responses to mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Various lipid-mediated signaling mechanisms are involved in the regulation of mitochondrial function. Examples include (254,287): (i) mitophagy, where CL translocates from the MIM to the MOM to bind LC3 and LC3-B-II in collaboration with CER to induce autophagosomal mitochondrial recruitment; (ii) ETC assembly, where the chaperone PHB2 involved in CIV assembly interacts with sphingosine-1phosphate (S1P); and (iii) apoptosis, where CER accumulates and acts together with Bax to induce pore formation, allowing cytochrome-c exit and apoptosis activation.…”
Section: B Role Of Mitochondrial Lipids In Mitochondrial (Ultra)strumentioning
confidence: 99%
“…Various lipid-mediated signaling mechanisms are involved in the regulation of mitochondrial function. Examples include (254,287): (i) mitophagy, where CL translocates from the MIM to the MOM to bind LC3 and LC3-B-II in collaboration with CER to induce autophagosomal mitochondrial recruitment; (ii) ETC assembly, where the chaperone PHB2 involved in CIV assembly interacts with sphingosine-1phosphate (S1P); and (iii) apoptosis, where CER accumulates and acts together with Bax to induce pore formation, allowing cytochrome-c exit and apoptosis activation.…”
Section: B Role Of Mitochondrial Lipids In Mitochondrial (Ultra)strumentioning
confidence: 99%
“…S1P production by hypoxia stimulated the glycolytic flux in erythrocytes through the release of a membrane-bound glycolytic enzyme, which is critical for the upregulating of hemoglobin's oxygen release capacity in erythrocytes 26,27 . In addition to the HIF1-regulated S1P metabolism, inhibition of sphingosine kinase 2, the isotype of mitochondrial S1P-producing enzyme, reduced oxidative stress through the suppression of Nrf2 accumulation, SOD2 expression, and mitochondrial respiration 51,52 . However, our data revealed that cP1P did not affect Nrf2 accumulation or SOD2 expression and acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…All these signals are candidate targets of potential obesogenic EDCs. Lipids, which role has been considered crucial in many tissues including liver, fat and intestine are accumulated and stored till their use in case of energy needs ( 5 ). Many studies so far have been carried out to reveal the pivotal role of dietary lipid intake as a source of essential fatty acids governing energy balance, food intake, growth, reproduction and health.…”
Section: Introductionmentioning
confidence: 99%